Baluteau, François, Dupriez, Vincent, Verhoeven, Marie (Éd.). (2018). Entre tronc commun et filières, quelle école moyenne? Étude comparative - Périsset, Danièle (Swiss Journal of Educational Research, 2019)
Recension